A simple physical phantom for an intercomparison exercise on 241Am activity determination in the skull - Vrba, T; Malátová, I; Fojtík, P; Fülöp, M; Ragan, P (Radiation protection dosimetry, 2014)
A simple hemispherical phantom has been designed and prepared for the EURADOS intercomparison exercise on (241)Am activity determination in the skull (2011-13). The phantom consists of three parts that substitute bone and soft tissues. (241)Am is deposited on the surfaces of the bone-substituting part. The design and assumed composition of phantom parts are discussed. A preparation of the voxel representation of the phantom is described. The spectrum of a real measurement of the physical phantom agrees well with the simulation. The physical phantom, and its voxel representation, is provided to the participants of the intercomparison exercise.
Keywords: Equipment Design; Radiation Monitoring; Americium; Tomography, X-Ray Computed; Radiometry; fantomy radiodiagnostické; Reproducibility of Results; americium; kosti a kostní tkáň; Calibration; Monte Carlo Method; fotony; Photons; Polyurethanes; radiometrie; Skull; kalibrace; reprodukovatelnost výsledků; monitorování radiace; metoda Monte Carlo; Czech Republic; Phantoms, Imaging; Česká republika; lebka; design vybavení; Bone and Bones; polyurethany; počítačová rentgenová tomografie